2016
DOI: 10.1038/srep28929
|View full text |Cite
|
Sign up to set email alerts
|

MINDEC-An Enhanced Negative Depletion Strategy for Circulating Tumour Cell Enrichment

Abstract: Most current methods of circulating tumour cell (CTC) enrichment target the epithelial protein EpCAM, which is commonly expressed in adenocarcinoma cells. However, such methods will not recover the fraction of CTCs that have a non-epithelial phenotype due to epithelial–mesenchymal transition. For phenotype-independent CTC enrichment, we developed a new enhanced negative depletion strategy—termed MINDEC—that is based on multi-marker (CD45, CD16, CD19, CD163, and CD235a/GYPA) depletion of blood cells rather than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 45 publications
0
38
0
Order By: Relevance
“…To date, several studies have been published on the molecular characterisation of single CTCs from different cancers, such as prostate, pancreatic and colorectal carcinomas [ 9 , 20 , 21 ]. In the current study, the single-cell quantitative PCR performance was validated by gene expression of GAPDH from the colon cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several studies have been published on the molecular characterisation of single CTCs from different cancers, such as prostate, pancreatic and colorectal carcinomas [ 9 , 20 , 21 ]. In the current study, the single-cell quantitative PCR performance was validated by gene expression of GAPDH from the colon cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Many groups have confirmed the presence of heterogeneous CTC phenotypes (such as epithelial, epithelium–mesenchymal transition (EMT) and mesenchymal/stem) in patients with different cancers, including CRC [ 6 , 7 ]. Interestingly, immunoaffinity-dependant negative selection techniques demonstrated higher efficacy in isolating heterogeneous CTCs from the blood of patients with cancer [ 8 , 9 ]. Molecular characterisation of the heterogeneous CTCs showed that they were more concordant with metastatic tumours than primary tumours in patients with colorectal cancers, suggesting the acquired characteristics of the CTCs in the blood microenvironment [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…CTCs are extremely rare compared with other cells in the blood of patients with cancer ( Fig . ), so extensive enrichment is required to detect them ( Table ). In general, enrichment is based on physical (such as size or density) or biological (for example presence of specific proteins) properties.…”
Section: Circulating Tumour Cellsmentioning
confidence: 99%
“…The simple concept of CTC analysis is to gather or detect small numbers of CTCs from among larger numbers of white blood cells. Existing techniques for CTC isolation can be divided into three types: antibody-, physical property-, and function-based approaches [ 22 , 23 , 24 ]. A recently established microfluidic method is based on CTC isolation techniques that divided into three types as above.…”
Section: Concept For Circulating Tumor Cells (Ctcs) Analysismentioning
confidence: 99%
“…Cell surface proteins are often used as targets in antibody-based CTC isolation methods. Because of the lack of a strictly tumor-specific antigen, epithelial-specific proteins—such as epithelial cell adhesion molecule (EpCAM)—are used for CTC-positive selection and antibodies against leukocyte-specific surface antigens, such as CD45, are used to deplete leukocytes [ 24 , 25 ]. Technologies based on physical properties dominate the field of CTC separation.…”
Section: Concept For Circulating Tumor Cells (Ctcs) Analysismentioning
confidence: 99%